Fundamentals of entrepreneurship (ENT 300) : Repertoire / Nur A’inaa Izzati Nazarihan … [et al.] - Nazarihan, Nur A’inaa Izzati; Jamel, Mohd Shafiq Aima; Pathe, Khuhaimy (2019)
Repertoire is the name that has been chosen by one of the partners in the company. Repertoire, by definition, means a stock of plays, dances, or items that a company or a performer knows or is prepared to perform. In daily life, we are constantly completing mundane daily tasks. We try to take these mundanities to the next level by providing quirky and fun everyday items, thus performing a performance for our audience to entertain them. The concept of having a merged art class with a stationery store is something relatively new in Kuching, which is one of the reasons why this business was chosen. Apart from offering art classes, our business also provides a membership program with a lifetime fee of RM10 and special discounts